Currency substitution and the stability of the Italian demand for money before the entry into the monetary union, 1972 - 1998 - Hannah Nielsen; Giuseppe Tullio; Jürgen Wolters (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
A money demand function for M2 is estimated for Italy for the period 1972-1998 within an error correction framework. This period has been characterized by major structural changes in the Italian financial system and by major changes in monetary policy. This study takes these changes into account. Moreover, currency substitution, especially between Italy and Germany is incorporated into the model. By accounting for structural breaks and currency substitution a stable money demand function can be found.
urn:nbn:de:kobv:11-10047928
Keywords: E41; C22; 330; Money demand; error correction model; structural changes